Kolaborasi Peran Guru dan Orang Tua dalam Mendukung Pembelajaran Anak Dengan Gangguan Tunarungu - Marnah; Fauzi Fadlianysah; Uvia Nursehah (Arus Jurnal Pendidikan, 2025)
This study aims to describe the collaboration between teachers and parents in supporting the learning of students with hearing impairments at Sekolah Khusus Negeri 02 Kota Serang. The background of this research is the limited consistency in learning strategies and communication between teachers and parents, even though effective collaboration can positively impact the academic and social development of hearing-impaired students. This research uses a qualitative approach with a case study method. The subjects of the study were a homeroom teacher and the parents of two hearing-impaired students. Data were collected through observation, in-depth interviews, and documentation. The results showed that collaboration between teachers and parents had been established through regular communication, mainly via WhatsApp groups and school meetings, as well as the use of visual media and sign language in the learning process. Challenges faced include the lack of standardized sign language, low frequency of face-to-face communication, and limited variety of learning media. The conclusion of this study states that improving the quality of collaboration, providing sign language training for parents, and aligning learning strategies between school and home can help optimize the learning outcomes of hearing-impaired students.